A method for recycling carbon negative electrode scraps
By using dibenzoyl peroxide-assisted subcritical treatment and flotation technology in the negative electrode scraps of lithium-ion batteries, efficient separation and recovery of graphite and conductive agents were successfully achieved, the problem of waste of graphite resources in the existing technology was solved, and a recycled graphite negative electrode material with better performance was obtained.
Patent Information
- Application Number
- CN202310211489.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-17
- Filing Date
- 2023-03-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The prior art is difficult to effectively recover and utilize graphite and conductive agents in the negative electrode scraps of lithium-ion batteries, resulting in waste of graphite resources.
The combination of dibenzoyl peroxide-assisted subcritical treatment method and flotation method is adopted to achieve efficient separation and recovery of graphite and conductive agents. Specific steps include pretreating the scraps in a subcritical state, followed by positive flotation treatment to collect graphite, and finally repairing the structure and properties of graphite by acid treatment and carbonization treatment.
The efficient recycling and utilization of graphite and conductive agent in the negative electrode scraps is achieved, and the recycled graphite negative electrode material with better performance is obtained, which improves the effective utilization rate of the material.
Smart Images

Figure BDA0004112859230000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials, and in particular relates to a method for recycling negative electrode scraps. Background Art
[0002] Lithium-ion battery is a secondary battery with excellent performance and is widely used in new energy vehicles, consumer batteries, grid energy storage and other fields. In particular, new energy vehicles have been developing rapidly at an annual growth rate of 60-80% in recent years, and the production capacity of power batteries has also expanded rapidly, and the entire lithium-ion battery industry has ushered in explosive growth. This has caused upstream battery materials, such as positive and negative electrode materials, to face the dual problems of insufficient supply and rising prices. How to improve the lean management of the battery production process, further improve the effective utilization rate of materials, and recycle the scraps generated during production has received more and more widespread attention.
[0003] There are coating and die-cutting processes in the production process of lithium-ion battery negative electrodes. Coating is to evenly apply a slurry mixed with graphite active materials, conductive carbon black, binders and other additives on the copper foil with a scraper. During die-cutting, the coated negative electrode will be cut into the required size, which will produce about 2-3% of negative electrode scraps, because these scraps are combined with the copper current collector, and the carbon components of the scraps usually inevitably contain binder and conductive agent components, and may even be mixed with diaphragms and siliceous dust. At present, most of the treatment of these scraps is just to recycle copper through powder mills, and the carbonaceous components are usually not used at a high price, resulting in a waste of graphite resources. Summary of the invention
[0004] In view of the problems existing in the recycling of existing negative electrode scraps, the first purpose of the present invention is to provide a method for recycling carbon negative electrode scraps, aiming to effectively recover graphite and other components therein.
[0005] The second object of the present invention is to provide a regenerated negative electrode obtained by the recycling method and its use in a lithium-ion battery.
[0006] The negative electrode scraps contain graphite, conductive agent, binder and other components. How to effectively separate the graphite and conductive agent is the main difficulty in improving the recycling value of the negative electrode scraps. To solve this problem, the present invention provides the following solutions:
[0007] A method for recycling carbon negative electrode scraps, comprising the following steps:
[0008] Step (1):
[0009] The carbon negative electrode scraps are dispersed in a treatment solution containing dibenzoyl peroxide and water and heated and pressurized to a subcritical state for pretreatment; then the pressure is released and the temperature is lowered to separate and obtain a pretreated material enriched with graphite and a carbonaceous conductive agent;
[0010] Step (2):
[0011] The pre-treated material is subjected to positive flotation treatment to collect the graphite floating material;
[0012] The positive flotation reagents include inhibitors, frothers and collectors;
[0013] The inhibitor is at least one of water glass, sodium metaphosphate, sodium thiosulfate and potassium dichromate;
[0014] The collector is at least one of sodium dodecyl sulfate and cyclohexane acid soap;
[0015] The foaming agent is an ether alcohol foaming agent;
[0016] Step (3):
[0017] The graphite obtained by flotation is treated with acid, washed to neutrality, and then combined with a carbon source for carbonization to obtain the regenerated carbon negative electrode.
[0018] In the present invention, a subcritical treatment method assisted by dibenzoyl peroxide and the flotation method are innovatively adopted to achieve efficient separation of graphite, copper and conductive agent, so that the components in the negative electrode scraps can be efficiently recycled and utilized. Not only that, graphite negative electrode materials with better performance can also be regenerated.
[0019] In the present invention, the dibenzoyl peroxide-assisted subcritical treatment can perform surface treatment on the components in the scraps, realize the dissociation of the components, amplify the physicochemical differences between the components, and further cooperate with flotation and the combined control of reagents, especially collectors and inhibitors, to realize the effective separation and utilization of graphite and conductive agents, repair the structure, improve the surface properties and active sites, and thus give the recycled materials better electrochemical properties.
[0020] In the present invention, the carbon negative electrode scraps are scraps produced in the production of lithium-ion battery negative electrodes. The scraps can be residues that have been previously recovered from copper, or scraps that have not been previously separated from copper.
[0021] Preferably, the carbon negative electrode scraps are crushed into powders of ≤1 mm in advance.
[0022] In the present invention, the subcritical treatment assisted by dibenzoyl peroxide helps to achieve the dissociation of components in the scraps and the surface differential modification, which is beneficial to the subsequent flotation synergy and improves the separation and regeneration performance.
[0023] Preferably, in the treatment solution, the weight content of dibenzoyl peroxide is 1 to 10%;
[0024] Preferably, the liquid-to-solid volume weight ratio of the carbon negative electrode scraps and the treatment liquid is 10-15 ml / g.
[0025] Preferably, in step (1), the subcritical state refers to a temperature of 250-300° C. and a pressure of 5-10 MPa.
[0026] In the present invention, after the subcritical treatment, a pressure relief and temperature reduction treatment is performed, and the pre-treated material can be separated based on existing methods such as screening treatment, and the size of the screen can be controlled according to needs.
[0027] In the present invention, under the subcritical modification treatment of dibenzoyl peroxide, further coordinated with the subsequent flotation process and the joint control of flotation parameters, it is beneficial to separate graphite and conductive agent and repair and modify the structure of graphite, which is beneficial to realize the regeneration of graphite and can obtain recycled materials with better performance.
[0028] In the present invention, there is no particular requirement for the type of the frother in the flotation reagent, as long as it can achieve frothering. For example, it can be an ether alcohol frother, more preferably at least one of methyl ether alcohol, ethyl ether alcohol, and butyl ether alcohol.
[0029] In the present invention, the dosage of the flotation reagent can be adjusted as needed. Considering the economic performance and value, preferably, in step (2), the dosage of the inhibitor is 10-20 g / t; the collector is 40-70 g / t; and the frother is 50-80 g / t. The dosage of the reagents is based on the weight of the pretreated material. For example, g / t refers to the dosage of the reagent per ton of pretreated material.
[0030] In the present invention, the floating material of the positive flotation is graphite, and the bottom material is conductive carbon, such as conductive carbon black.
[0031] In the present invention, the graphite obtained by positive flotation is treated with acid. The acid used in the acid treatment stage is an aqueous solution of at least one of hydrochloric acid, nitric acid and hydrofluoric acid;
[0032] Preferably, the acid solution is an aqueous solution of hydrochloric acid, nitric acid and hydrofluoric acid;
[0033] More preferably, in the acid solution, the concentration of hydrochloric acid is 1-3M, the concentration of nitric acid is 0.5-1M, and the concentration of hydrofluoric acid is 0.2-0.5M.
[0034] In the present invention, the recycled graphite is subjected to surface carbon coating treatment to obtain the regenerated graphite material.
[0035] Preferably, the carbon source is at least one of tannic acid, citric acid, chlorogenic acid and alginic acid;
[0036] In the present invention, the graphite and the carbon source may be compounded in the form of solid mixing or liquid mixing.
[0037] Preferably, the mass ratio of the flotation graphite to the carbon source is 10-20:1.
[0038] Preferably, the carbonization atmosphere is a protective atmosphere;
[0039] Preferably, the carbonization temperature is 550-1000°C, more preferably 600-700°C;
[0040] Preferably, the carbonization time is 1 to 3 hours.
[0041] A further preferred embodiment of the present invention comprises the following steps:
[0042] The first step is to crush the scraps into powders ≤ 1 mm, and then prepare a subcritical reaction aqueous solution with a BPO concentration of 1-10%, add the powder and the aqueous solution into a subcritical high-pressure reactor for reaction, with a liquid-to-solid ratio of 10-15:1, a temperature of 250-300°C, and a pressure of 5-10MPa;
[0043] In the second step, the powder from the first step is subjected to flotation treatment to separate the graphite component from the carbonaceous conductive agent component. Inhibitors, collectors and frothers should be added during flotation. The inhibitor is at least one of water glass, sodium metaphosphate, sodium thiosulfate and potassium dichromate; the collector is at least one of sodium dodecyl sulfate and cyclohexane acid soap; the frother is an ether alcohol frother, specifically at least one of methyl ether alcohol, ethyl ether alcohol and butyl ether alcohol. 10-20g of inhibitor, 40-70g of collector and 50-80g of frother are added to each ton of the material to be floated, and graphite is obtained by flotation; the flotation process can be repeated 2-4 times as needed.
[0044] The third step is to purify the graphite obtained by flotation in a triacid solution consisting of hydrochloric acid, nitric acid and hydrofluoric acid;
[0045] The fourth step is to coat the powder with liquid carbon. Tannic acid is selected as the carbon source, deionized water is used as the solvent, the mass ratio of the carbon source to the powder is 1:10-20, the water is removed at high temperature after being fully mixed, and then carbonization is performed to obtain the prepared high-performance recycled graphite negative electrode.
[0046] The invention also provides a regenerated carbon negative electrode prepared by the method.
[0047] The preparation method of the present invention can give the regenerated material special physical and chemical characteristics, and the regenerated carbon negative electrode prepared by the preparation method can show excellent electrochemical properties.
[0048] The present invention also provides a negative electrode of a lithium ion battery, comprising a current collector and a negative electrode material composited on the surface of the current collector, wherein the negative electrode material comprises the regenerated carbon negative electrode prepared by the method.
[0049] The invention also provides a lithium ion battery, the negative electrode of which is the negative electrode described above.
[0050] Beneficial effects:
[0051] In the present invention, a subcritical treatment method assisted by dibenzoyl peroxide and the flotation method are innovatively adopted to achieve efficient separation of graphite, copper and conductive agent, so that the components in the negative electrode scraps can be efficiently recycled and utilized. Not only that, graphite negative electrode materials with better performance can also be regenerated. DETAILED DESCRIPTION
[0052] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited thereto.
[0053] The raw materials of this embodiment come from the scraps of negative electrode foil die-cutting in lithium-ion battery factories, and contain copper foil, binder, conductive agent, graphite and other additives.
[0054] Example 1
[0055] ① First, the scraps are crushed into powders ≤ 1 mm, and then a subcritical reaction aqueous solution with a BPO concentration of 2 wt% is prepared. The powder and the aqueous solution are added to a subcritical high-pressure reactor for reaction at a liquid-solid ratio of 15:1, a temperature of 300 ° C, and a pressure of 10 MPa. The temperature is then reduced and the pressure is released, and the carbon material is obtained by screening and filtering;
[0056] ② The first step powder is subjected to flotation treatment. The flotation reagents include inhibitors, collectors and frothers, wherein the inhibitor is sodium metaphosphate; the collector is sodium dodecyl sulfate; the frother is methyl ether alcohol. 10g / t of inhibitor, 50g / t of collector and 75g / t of frother are added to each ton of carbon material, and stirred for 10 minutes to obtain a flotation foam product containing recovered graphite and a flotation bottom material containing conductive carbon black.
[0057] ③ The graphite obtained by flotation is placed in an acid solution for treatment, wherein the acid solution is a mixed aqueous solution of 1M HCl, 0.5M HNO3 and 0.2M HF, and the liquid-to-solid ratio of the acid solution to the graphite is 10mL / g; the treatment time is 2h, and after the treatment, the solid-liquid separation and water washing to neutrality are performed to obtain graphite material A;
[0058] ④ The above-mentioned graphite material A powder and tannic acid are mixed in a mass ratio of 12:1 and dissolved in water, followed by solid-liquid separation and drying to obtain a precursor, which is then carbonized at 600°C for 3 hours under an Ar atmosphere to obtain the prepared high-performance recycled graphite negative electrode.
[0059] Example 2
[0060] ① First, the scraps are crushed into powders ≤ 1 mm, and then a subcritical reaction aqueous solution with a BPO concentration of 5wt% is prepared. The powder and the aqueous solution are added to a subcritical high-pressure reactor for reaction at a liquid-to-solid ratio of 12:1, a temperature of 275°C, and a pressure of 7.5MPa. The temperature is then reduced and the pressure is released, and the carbon material is obtained by screening and filtering;
[0061] ② The first step powder is subjected to flotation treatment. The flotation reagents include inhibitors, collectors and frothers, wherein the inhibitor is sodium thiosulfate; the collector is sodium dodecyl sulfate; the frother is ethyl ether alcohol. 15g / t of inhibitor, 60g / t of collector and 60g / t of frother are added to each ton of carbon material, and stirred for 10 minutes to obtain a flotation foam product containing recovered graphite and a flotation bottom material containing conductive carbon black.
[0062] ③ The graphite obtained by flotation is placed in an acid solution for treatment, wherein the acid solution is a mixed aqueous solution of 2M HCl, 1M HNO3 and 0.5M HF, and the liquid-to-solid ratio of the acid solution to the graphite is 15mL / g; the treatment time is 2h, and after the treatment, the solid-liquid separation and water washing to neutrality are performed to obtain graphite material A;
[0063] ④ The above-mentioned graphite material A powder and tannic acid were mixed in a mass ratio of 15:1 and dissolved in water, followed by solid-liquid separation and drying to obtain a precursor, which was then carbonized at 700°C for 2h under an Ar atmosphere to obtain the prepared high-performance recycled graphite negative electrode.
[0064] Example 3
[0065] ① First, the scraps are crushed into powders ≤ 1 mm, and then a subcritical reaction aqueous solution with a BPO concentration of 10wt% is prepared. The powder and the aqueous solution are added to a subcritical high-pressure reactor for reaction at a liquid-solid ratio of 10:1, a temperature of 255°C, and a pressure of 5MPa. The temperature is then reduced and the pressure is released, and the carbon material is obtained by screening and filtering;
[0066] ② The first step powder is subjected to flotation treatment. The flotation reagents include an inhibitor, a collector and a frother, wherein the inhibitor is potassium dichromate; the collector is decacyclohexane acid soap; the frother is butyl ether alcohol. 20g / t of inhibitor, 40g / t of collector and 50g / t of frother are added to each ton of carbon material, and stirred for 10 minutes to obtain a flotation foam product containing recovered graphite and a flotation bottom material containing conductive carbon black.
[0067] ③ The graphite obtained by flotation is placed in an acid solution for treatment, wherein the acid solution is a mixed aqueous solution of 1.5M HCl, 0.5M HNO3 and 0.3M HF, and the liquid-to-solid ratio of the acid solution to the graphite is 15mL / g; the treatment time is 2h, and after the treatment, the solid-liquid separation and water washing to neutrality are performed to obtain graphite material A;
[0068] ④ The graphite material A powder and tannic acid were mixed in a mass ratio of 18:1 and dissolved in water, followed by solid-liquid separation and drying to obtain a precursor, which was then carbonized at 650°C in an Ar atmosphere for 1.5h.
[0069] Comparative Example 1
[0070] Compared with Example 1, the only difference is that BPO is not added to the initial subcritical solution in ①.
[0071] Comparative Example 2
[0072] Compared with Example 1, the only difference is that in the initial subcritical solution of ①, acetic anhydride is used to replace BPO.
[0073] Comparative Example 3
[0074] Compared with Example 1, the only difference is that the pressure and temperature of ① reach a supercritical state, for example, the temperature is 400° C. and the pressure reaches 25 MPa.
[0075] Comparative Example 4
[0076] Compared with Example 1, the only difference is that in the flotation reagent, an equal amount of kerosene replaces the collector, and other operations and parameters are the same as in Example 1.
[0077] Performance Testing
[0078] The electrode materials prepared in the above-mentioned embodiments 1 to 3 and comparative examples 1 to 4 are made into electrode slurry. The slurry ratio is electrode material: binder (PAA): conductive agent (SP) = 80:10:10. After the slurry is stirred evenly, it is coated on the copper foil and then dried under vacuum. The dried electrode sheet is used as the working electrode of the button battery, the lithium sheet is used as the counter electrode, and the electrolyte is 1 mol / L lithium hexafluorophosphate (LiPF6) electrolyte dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) electrolyte with a volume ratio of 1:1. The constant current charge and discharge voltage range is 0.01 to 1.5V. And cycle 300 times at 0.2C and 65°C to obtain the cycle retention rate at high temperature. In addition, a high-temperature storage performance test will be carried out, specifically: first discharge the battery to 0.005V, that is, the graphite is completely embedded with lithium. Then store it at 65°C for 30 days, test its capacity again, and calculate the capacity recovery rate (capacity after high-temperature storage / initial capacity before storage * 100%). The results at high temperature are shown in Table 1:
[0079] Table 1: Test results of examples and comparative examples
[0080]
[0081] Note: [a] The negative electrode material obtained by stripping the copper foil of the scraps in Example 1 and PAA were mixed in a weight ratio of 90:10 to prepare a negative electrode, and the performance test was carried out using the method of Example 1.
[0082] In the present invention, by combining the processes and parameters, synergy can be achieved, and excellent electrochemical performance can be obtained, especially excellent high-temperature long-range cycling and high-temperature storage stability.
Claims
1. A method for recycling carbon negative electrode scraps, characterized in that the steps include: Step (1): The carbon negative electrode scraps are dispersed in a treatment solution containing dibenzoyl peroxide and water and heated and pressurized to a subcritical state for pretreatment; then the pressure is released and the temperature is lowered to separate and obtain a pretreated material enriched with graphite and a carbonaceous conductive agent; Step (2): The pre-treated material is subjected to positive flotation treatment to collect the graphite floating material; The positive flotation reagents include inhibitors, frothers and collectors; The inhibitor is at least one of water glass, sodium metaphosphate, sodium thiosulfate and potassium dichromate; The collector is at least one of sodium dodecyl sulfate and cyclohexane acid soap; Step (3): The graphite obtained by flotation is treated with acid, washed to neutrality, and then combined with a carbon source for carbonization to obtain the regenerated carbon negative electrode.
2. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: The carbon negative electrode scraps are scraps generated in the production of lithium-ion battery negative electrodes.
3. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: Crush the carbon negative electrode scraps into powder ≤1mm in advance.
4. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: In the treatment solution, the weight content of dibenzoyl peroxide is 1 to 10%.
5. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: The liquid-to-solid volume weight ratio of the carbon negative electrode scraps and the treatment liquid is 10-15 ml / g.
6. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: In step (1), the subcritical state refers to a temperature of 250-300°C and a pressure of 5-10 MPa.
7. The method for recycling carbon negative electrode scraps as claimed in claim 1, characterized in that: In step (2), the foaming agent is an ether alcohol foaming agent.
8. The method for recycling carbon negative electrode scraps as claimed in claim 7, characterized in that: In step (2), the foaming agent is at least one of methyl ether alcohol, ethyl ether alcohol and butyl ether alcohol.
9. The method for recycling carbon negative electrode scraps as claimed in claim 1, characterized in that: In step (2), the dosage of the inhibitor is 10-20 g / t; the dosage of the collector is 40-70 g / t; and the dosage of the foaming agent is 50-80 g / t.
10. The method for recycling carbon negative electrode scraps as claimed in claim 1, characterized in that: The acid solution used in the acid treatment stage is an aqueous solution of at least one of hydrochloric acid, nitric acid and hydrofluoric acid.
11. The method for recycling carbon negative electrode scraps according to claim 10, characterized in that: The acid solution is an aqueous solution of hydrochloric acid, nitric acid and hydrofluoric acid.
12. The method for recycling carbon negative electrode scraps according to claim 10, characterized in that: In the acid solution, the concentration of hydrochloric acid is 1~3M, the concentration of nitric acid is 0.5~1M, and the concentration of hydrofluoric acid is 0.2~0.5M.
13. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: The carbon source is at least one of tannic acid, citric acid, chlorogenic acid and alginic acid.
14. The method for recycling carbon negative electrode scraps according to claim 1, characterized in that: The mass ratio of the flotation graphite to the carbon source is 10-20:
1.
15. The method for recycling carbon negative electrode waste material according to claim 1, characterized in that: The carbonization atmosphere is a protective atmosphere.
16. The method for recycling carbon negative electrode edge waste according to claim 1, characterized in that: The carbonization temperature is 550~1000℃.
17. The method for recycling carbon negative electrode waste material according to claim 1, characterized in that: The carbonization time is 1~3h.
18. A regenerated carbon negative electrode prepared by the method according to any one of claims 1 to 17.
19. A negative electrode of a lithium ion battery, comprising a current collector and a negative electrode material composited on the surface thereof, characterized in that: The negative electrode material comprises a regenerated carbon negative electrode prepared by the method according to any one of claims 1 to 17.
20. A lithium ion battery, characterized in that: The negative electrode is the negative electrode as claimed in claim 19.
Citation Information
Patent Citations
Long-circulation graphite negative electrode active material, preparation thereof and application of long-circulation graphite negative electrode active material in lithium secondary battery
CN115498168A
Graphite negative electrode material for high-performance lithium ion battery and preparation method therefor
WO2021189836A1